2021
DOI: 10.3389/fonc.2021.646060
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Gene SERPINE1 Is a Novel Biomarker for Diffuse Lower-Grade Gliomas via Large-Scale Analysis

Abstract: BackgroundGlioma is one of the highly fatal primary tumors in the central nervous system. As a major component of tumor microenvironment (TME), immune cell has been proved to play a critical role in the progression and prognosis of the diffuse lower-grade gliomas (LGGs). This study aims to screen the key immune-related factors of LGGs by investigating the TCGA database.MethodsThe RNA-sequencing data of 508 LGG patients were downloaded in the TCGA database. ESTIMATE algorithm was utilized to calculate the strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 62 publications
5
24
0
1
Order By: Relevance
“…Previous studies showed that SERPINE1 had focused on its effect on thrombosis in humans [ 10 ]. Using high-throughput sequencing technology, SERPINE1 was found to be significantly overexpressed in a variety of tumor tissues [ 11 ]. It has been reported that SERPINE1 can be used as a proliferation regulator of glioblastoma, and its high expression can promote the proliferation and invasion of glioma cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that SERPINE1 had focused on its effect on thrombosis in humans [ 10 ]. Using high-throughput sequencing technology, SERPINE1 was found to be significantly overexpressed in a variety of tumor tissues [ 11 ]. It has been reported that SERPINE1 can be used as a proliferation regulator of glioblastoma, and its high expression can promote the proliferation and invasion of glioma cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…After conducting WGCNA, a total of 45 potential hub genes were identified. Lu et al used CytoHubba MCC method in their study to screen out hub genes, whereas Huang et al identified serpin family E member 1 (SERPINE1) as a novel biomarker for diffuse lower-grade gliomas via CytoHubba stress algorithm and CytoHubba betweenness algorithm (49,50). Considering that all these algorithms were effective methods to screen out hub genes, we screened out three hub genes among the 45 genes by using all the algorithms in the present study to make our results credible.…”
Section: Discussionmentioning
confidence: 90%
“…Glioma is a highly fatal primary tumor of the central nervous system. Despite diverse available therapeutic strategies, including surgery, chemotherapy, and immunotherapy, the median survival of people with glioma—which has barely improved since its recognition as a separate cancer type—remains only approximately 14 months ( Huang et al, 2021 ). Therefore, more sensitive and specific diagnostic biomarkers and potential therapeutic targets for glioma patients are of no delay.…”
Section: Discussionmentioning
confidence: 99%